Use of fully covered self-expanding metal biliary stents for managing endoscopic biliary sphincterotomy related bleeding - Bilal, Mohammad; Chandnani, Madhuri; McDonald, Nicholas M.; Miller, Corey S.; Saperia, James; Wadhwa, Vaibhav; Singh, Shailendra; Cohen, Jonah M.; Berzin, Tyler M.; Sawhney, Mandeep S.; Pleskow, Douglas K. (Endoscopy International Open, 2021)
Background and study aims Endoscopic biliary sphincterotomy (EBS) related-bleeding is a common adverse event related to endoscopic retrograde cholangiopancreatography (ERCP). Traditionally, endoscopic modalities such as epinephrine injection, cauterization, and balloon tamponade have been used for management. Recently, use of a fully covered self-expandable metal stent (FCSEMS) to manage EBS-related bleeding has gained popularity. However, data regarding its use are limited to small case series. Therefore, we aimed to evaluate the safety and efficacy of FCSEMS placement for the treatment of EBS-related bleeding.Patients and methods All patients referred to our center from October 2014 to November 2019 who had an FCSEMS placed for EBS-related bleeding were included. FCSEMS was placed either for primary control of bleeding or after failure of other traditional endoscopic hemostasis techniques at the discretion of the endoscopist. Data was collected regarding patient demographics, procedural characteristics, clinical and technical success rates of FCSEMS, as well as adverse events.Results A total of 97 patients underwent placement of FCSEMS for EBS-related bleeding, of which 76.3 % had immediate bleeding and 23.7 % had delayed bleeding. Mean age was 67.2 years and 47.4 % were males. Seven patients who had immediate EBS-related bleeding at index ERCP underwent other endoscopic therapies prior to placement of FCSEMS for rebleeding. The technical success rate for FCSEMS placement was 100 % and the rebleeding rate was 6.2 %. Four patients with FCSEMS placement developed pancreatitis and four had stent migration.Conclusions Our findings suggest that FCSEMS is a highly effective treatment modality for managing EBS-related bleeding and has an acceptable safety profile.